2018
DOI: 10.1007/s11036-018-1140-x
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Rule-Based Distributed Reasoning Framework for Resource-bounded Systems

Abstract: Over the last few years, context-aware computing has received a growing amount of attention among the researchers in the IoT and ubiquitous computing community. In principle, context-aware computing transforms a physical environment into a smart space by sensing the surrounding environment and interpreting the situation of the user. This process involves three major steps: context acquisition, context modelling, and context-aware reasoning. Among other approaches, ontologybased context modelling and rule-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As a result, we must establish algorithms/standards to regulate this situation. The [8] present study has further refined the previous models of context-aware systems [8], which were developed for resource-constrained devices using rule-based systems based on the logical framework [9]. The improvement in this research lies in developing new calculation methods for memory allocation.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…As a result, we must establish algorithms/standards to regulate this situation. The [8] present study has further refined the previous models of context-aware systems [8], which were developed for resource-constrained devices using rule-based systems based on the logical framework [9]. The improvement in this research lies in developing new calculation methods for memory allocation.…”
Section: Introductionmentioning
confidence: 76%
“…In the early works in Pervasive and Ubiquitous Computing, context awareness is referred to as the location of the objects and/or people [11]. In recent years, the context has been extended to other factors, such as the social and physical aspects of an entity and the activities of the user [8], [12], [13]. Similarly, [11], [14]- [19] evaluated the user's identity and social situation, as well as the user's location, environmental and/or temporal information, the objects and people in their immediate surroundings, as well as any changes to those objects.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the development of context-aware applications for reasoning on resource-bounded mobile devices is challenging. Rakib & Uddin (2019) presented a context-aware framework with a lightweight rule engine and a wide range of user preferences to decrease the number of rules while inferring personalized contexts. The authors confirmed that associated rules can be reduced in order to enhance the inference engine efficiency in terms of accuracy, execution speed, total execution time, and execution cost.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Distributed reasoning is a central aspect required by many applications proposed in the last decades, including mobile and ubiquitous systems, smart spaces and Ambient Intelligence systems [1][2][3] -and more recently the Internet of Things (IoT) [4,5] -and the Semantic Web [6]. In these types of systems, distributed entities, called agents, are able to capture or receive information from their environment and from other agents, and are often able to derive new knowledge or making decisions based on the available knowledge.…”
Section: Introductionmentioning
confidence: 99%